Optimizing coffee harvest quality through smart farming with IoT-based portable solar dryer - Alya As Zahra Putri Fauzi; Hanif Alamudin Manshur; Elfi Anis Saati (Universitas Muhammadiyah Malang, 2025)
Coffee is one of the leading commodities in Harjokuncaran Village, South Malang, Indonesia, which is known as one of the robusta coffee-producing centers in Indonesia. The annual production is 1.5 tons/year in 4 harvests, with the peak harvest in July to August. Despite its great potential, the drying process is still conventionally done using solar heat without optimal control. This method takes a long time, and the results do not always meet the moisture content standards set by the Indonesian National Standard (SNI), so it is considered less efficient. This dedication program through PPK Ormawa is carried out to produce a coffee dryer with the help of technology in the Internet of Things (IoT) to produce quality according to SNI and increase quantity. The portable solar dryer is designed with a capacity of 80-100kg and a disassembly system, making it easy to move. The advantages of this dryer include energy efficiency, stable temperature at 50°C, and minimal contamination. In addition, the drying process is faster, from 7-14 days to 3-4 days. The methods used were tool design, training, mentoring, and testing of coffee beans in the Sucofindo laboratory. In addition, 25 farmers filled out questionnaires to determine the farmers' responses and understanding of the tool's operation, maintenance, and application usage. In addition, the results of testing coffee beans show that they follow SNI for conventional and use drying equipment. These findings indicate that the IoT-based dryer innovation has the potential to be a sustainable solution in increasing the quantity and quality of postharvest coffee.